THE CULTURE OF READING IN THE CURRENT UZBEK FAMILY: PROBLEMS AND SOLUTIONS - Bakhtiyor Robiddinovich Isakov (Galaxy International Interdisciplinary Research Journal, 2022)
This article analyzes the culture of reading in the Uzbek family, which is one of the most pressing problems today. In the article, the author pointed out that only reading, that is, enlightenment, can save humanity from various material and spiritual threats. According to the author, it is true that the low level of reading culture in Uzbek families is influenced by various threats (Internet, market economy, ideological threats, etc.) as well as internal problems in the spiritual environment of families.